Sociocultural Influence on English Language Skills of Secondary Students in Public Schools of Bardiya District in Nepal - Paudel, Kamal (CMC Journal, 2026)
The purposes of this study were to identify sociocultural factors influencing English language skills and to provide suggestions for improving them by examining the sociocultural aspects affecting public secondary students' narratives in Nepal, thereby understanding their realities, challenges, and opportunities in learning English. In this study, three students from a public secondary school in the Bardiya district, Nepal, were selected as research participants. The participants were interviewed in person using an open-ended questionnaire to elicit research information. The study contains the leading research questions: i. What are the influences of the sociocultural environment on English language skills, and ii. How have secondary students perceived sociocultural factors in terms of learning English language skills? This qualitative study selected research participants following a purposive, non-random sampling procedure. The major findings of this study suggest that complex, interconnected sociocultural factors influence the English language skills of Nepalese public secondary students. Sociocultural factors, including family and peer support, significantly affect English language skills. It stresses the requirement of supportive and competent English teachers. Similarly, it suggests that the success of Nepalese public secondary students in acquiring English skills largely relies on a complex interplay among family, friends, community, education system, and media to address challenges.